Effect of BMI on safety of bariatric surgery during the COVID-19 pandemic, procedure choice, and safety protocols – An analysis from the GENEVA Study. Issue 3 (May 2022) - Singhal, Rishi; Omar, Islam; Madhok, Brijesh; Ludwig, Christian; Tahrani, Abd A.; Mahawar, Kamal; ,; Pędziwiatr, Michał; Major, Piotr; Zarzycki, Piotr; Pantelis, Athanasios; Lapatsanis, Dimitris P.; et al.
Abstract: Background: It has been suggested that patients with a Body Mass Index (BMI) of > 60 kg/m 2 should be offered expedited Bariatric Surgery (BS) during the Coronavirus Disease-2019 (COVID-19) pandemic. The main objective of this study was to assess the safety of this approach. Methods: We conducted a global study of patients who underwent BS between 1/05/2020 and 31/10/2020. Patients were divided into three groups according to their preoperative BMI - Group I (BMI<50 kg/m 2 ), Group II (BMI 50–60 kg/m 2 ), and Group III (BMI>60 kg/m 2 ). The effect of preoperative BMI on 30-day morbidity and mortality, procedure choice, COVID-19 specific safety protocols, and comorbidities was assessed. Results: This study included 7084 patients (5197;73.4 % females). The mean preoperative weight and BMI were 119.49 ± 24.4 Kgs and 43.03 ± 6.9 Kg/m 2, respectively. Group I included 6024 (85 %) patients, whereas Groups II and III included 905 (13 %) and 155 (2 %) patients, respectively. The 30-day mortality rate was higher in Group III (p = 0.001). The complication rate and COVID-19 infection were not different. Comorbidities were significantly more likely in Group III (p = <0.001). A significantly higher proportion of patients in group III received Sleeve Gastrectomy or One Anastomosis Gastric Bypass compared to other groups. Patients with a BMI of > 70 kg/m 2 had a 30-day mortality of 7.7 % (2/26). None of these patients underwent a Roux-en-Y Gastric Bypass. Conclusion: The 30-day mortality rate was significantly higher in patients with BMI > 60 kg/m 2 . There was, however, no significant difference in complications rates in different BMI groups, probably due to differences in procedure selection. Highlights: This study included 7084 patients (5197;73.4 females). The mean preoperative weight and BMI were 119.49 ± 24.4 Kgs and 43.03 ± 6.9 Kg/m 2, respectively. The 30-day mortality rate was significantly higher in patients with BMI > 60 kg/m 2 . There was however no significant difference in complications rates in different BMI groups, probably due to differences in procedure selection. Patients with a BMI of > 70 kg/m 2 had a 30-day mortality of 7.7 % (2/26).